Bond strength and cytotoxicity of a universal adhesive according to the hybridization strategies to dentin - Leite, Maria Luísa de Alencar e Silva [UNESP]; Costa, Carlos Alberto de Souza [UNESP]; Duarte, Rosângela Marques; de Andrade, Ana Karina Maciel; Soares, Diana Gabriela [UNESP] (FapUNIFESP (SciELO), 2018)
This study evaluated application protocol (etch-and-rinse/ER and self-etching/SE) and dentin wettability (wet and dry) on microtensile bond strength (µTBS) and transdentinal cytotoxicity of Scotchbond™ Universal (SU) adhesive system. The µTBS values and fracture mode were registered 24 h after adhesive system application and resin composite block build-up (n=5). For analysis of transdentinal cytotoxicity, odontoblast-like MDPC-23 cells were seeded on pulpal surface of dentin discs (0.4 mm thick) adapted to artificial pulp chambers (n=8). The adhesive system was applied to occlusal surface, followed by 24-h incubation time. Cell viability (Alamar Blue) and morphology (SEM) were assessed. Adper Single Bond 2 and Clearfil SE Bond were used as positive controls of the ER and SE application protocols, respectively. No treatment was performed on negative control (NC) group. Data were analyzed by ANOVA and Tukey’s tests (α=5%). Higher mTBS values were found for ER mode in comparison with SE protocol (p<0.05). Dentin wettability had no effect on bond strength of SU in both the ER and SE techniques (p>0.05). Most fractures involved hybrid layer and/or adhesive layer. Neither variable prevented the intense toxic effects of adhesive systems on MDPC-23 cultured cells, since intense reduction in cell viability (±88%) and severe alterations in cell morphology were observed for all groups compared to NC, with no differences among them (p>0.05). Therefore, it was concluded that application of SU following the ER protocol had better adhesive performance. However, this adhesive system featured intense transdentinal cytotoxicity to pulp cells, regardless of application protocol and dentin wettability.
Keywords: Adhesive system; Bond strength; Cytotoxicity; Pulp cell